Analisis psikologis novel negeri 5 menara karya Ahmad Fuaddi - Aziz, Abdul (2021)
Abstrak Literature is a figurative picture of a person and produces a life colored by attitude. Thus, literary works can be approached using a psychological approach. The problem of this research is about psychology in the novel Negeri Lima Menara by Ahmad Fuadi. This study aims to find out the description of the psychological description of the character Alif in the novel Negeri 5 Menara by Ahmad Fuadi which amounted to 425 pages. Publisher PT Gramedia Pustaka Utama, Jakarta. 2009. This research data is in the form of a psychological picture of Alif's character. The method used is descriptive method with qualitative analysis by describing the psychological picture of Alif in the novel Negeri 5 Menara by Ahmad Fuadi with a Psychological Approach. This method is based on consideration of the suitability of the research form with the research objectives. The research instrument was carried out by means of a documentation study. Documentation study was conducted on the novel Negeri 5 Menara by Ahmad Fuadi with a Psychological Approach. From the results of this study, information can be obtained that the description of Alif's character is angry, anxious, afraid, depressed, hesitant and indecisive.